IMPLEMENTASI KEBIJAKAN PENGENDALIAN DAN PENGAWASAN MINUMAN BERALKOHOL DI KABUPATEN MINAHASA TENGGARA (Studi di Kecamatan Touluaan Kabupaten Minahasa Tenggara) - Bataren, Stevi; RUMAPEA, PATAR; KIYAI, BURHANUDDIN (JURNAL ADMINISTRASI PUBLIK, 2018)
The main task of the government is to create policy through various public policy. Policy will be achieved ifthe policies made are implemented or implemented properly. Successful implementation of a policy isdetermined by many variables or factors, both regarding the content of the implemented policy, theimplementation of the policy, and the environment in which the policy is implemented (the target group). Thepurpose of this research is to know the Implementation of Alcoholic Beverage Control and Control Policy inSoutheast Minahasa Regency (Study in Touluaan District). The model used is descriptive with qualitativeapproach. Informants in the study are people who can provide information about the situation and conditionof the research background. with the focus of research in view of the indicator according to Edwards III,namely communication, resources, disposition and bureaucratic structure. Data collection techniques used areobservation, interview, and documentation. The results of this study show the general picture on theImplementation of Alcohlic Drink Control and Supervision Policy in Southeast Minahasa Regency (Study inTouluaan District) has not been implemented well. Due to the lack of information dissemination in terms ofwidespread socialization to the community and has not been able to provide a thorough understanding of theimportance of the implementation of the Regional Regulation, as well as inadequate resources, in this case thecause of non-execution of the policy perfectly.Keywords: Policy Implementation, Controlling and Supervision, Alcoholic Beverages